The moisture buffering performance of plasters when exposed to simultaneous sinusoidal temperature and RH variations. (February 2021) - Cascione, Valeria; Maskell, Daniel; Shea, Andy; Walker, Pete
Abstract: Wall constructions have the capacity to contribute to the passive regulation of indoor Relative Humidity. This property, referred to as moisture buffering, is linked to the hygroscopicity of materials, which allows materials to store and release moisture from and to the surrounding air, depending on the indoor Relative Humidity levels. Laboratory testing procedures, based on a step-response method, were introduced to quantify moisture buffering. The step response method monitors the change in mass of samples, when subjected to square wave humidity variation and constant temperature. However, those protocol's prescribed testing environmental conditions may not be representative of the materials behaviour in buildings, as the surface of walls is exposed to an indoor environment that changes with respect to the temperature and humidity daily and seasonally. This paper investigates the response of clay and gypsum plasters to quasi sinusoidal and simultaneous humidity and temperature functions. It was experimentally shown that the relative humidity influences the amount of water vapour adsorbed and desorbed by the materials, while temperature impacts the rate and the time lag response of clay and gypsum to the indoor humidity variation. The significance of the investigation is to demonstrate the joint effects of Relative Humidity and temperature on hygroscopic materials and to seek to developing a laboratory test, which can represent the real behaviour of such materials in buildings, which are exposed to sine wave-forms. Abstract : The response of plasters to sinusoidal and simultaneous RH and temperature functions was tested. RH is significant in determining the amount of vapour adsorbed and desorbed by the materials. Temperature determines the time delay of the response of plasters to RH fluctuations. The pores structure of the materials determines the different response to the indoor climate variations. The study highlighted the unsuitability of the MBV for temperature sinusoidal variations.